Sea surface features and internal waves in the sea (MAUSAM, 1959)
On several oceanographic cruises conducted by Andhra University, an unusual sea-surface phenomenon was observed which consisted of long streaks of alternately smooth and rough water. On one occasion at the northern end of "Swatch of No Ground", temperature structure was measured at the same time as a passing of such series of wide sea surface streaks.